Otimização do uso de metacaulinita em misturas concreto: critérios de durabilidade, tecnológicos e microestruturais - Silva, Aluizio Caldas e (2019)
CHESF is the biggest Brazilian electricity generator with 10.7 GH of potential available in hydropower plants and widfarms. This number is related to 9,1% of the whole Brazilian demand. Some of its concrete structures are affetd by AAR causing several technical and economics issues. Regarding that consequences, the company is carrying researches to find this problem mitigation and prevent futures issues in new strutctures. Pozolanic materiais are used such as adittion to prevent AAR. Its minerals constituints are SiO2, o Al2O3 e o Fe2O3 and, mainly aluminiun is important to prevent a formation of hydrated expansive products. But, the RAA brazilian test methods and their concrete mix design using only conventional technical to select the materials raws and to prevent AAR development. In despite, under some specific situations those technics are not enough. It could be carry on to not effective answers. The aim of this Project was regard microstructural and non desctrutive technics to apply during material raw selection, including mineralogical and chemical composition.